Safety and Efficacy of Heparinization During Mechanical Thrombectomy in Acute Ischemic Stroke - Yang, Ming; Huo, Xiaochuan; Gao, Feng; Wang, Anxin; Ma, Ning; Liebeskind, David S.; Wang, Yongjun; Miao, Zhongrong (Frontiers in Neurology, 2019)
Background: The benefits of heparization during mechanical thrombectomy (MT) with newer generation thrombectomy devices, and if it is counterbalanced by the increased risk of intracranial hemorrhage (ICH) remain unknown. Methods: We included eligible patients who underwent MT from the ANGEL registry study (2015-2017) in China. Subjects in the current analysis were dichotomized into two groups according to whether adequate heparinization during MT was performed. In the heparinization group, unfractionated heparin was infused at 50–100 IU/Kg at first and additional 1,000 IU at intervals of an hour during the operation. Safety outcomes (symptomatic intracerebral hemorrhage [sICH], ICH and distal embolization) and efficacy outcomes (artery recanalization and functional outcomes at 3-month follow-up) were compared between groups. Results: We included 619 patients from the entire cohort of 917 patients. The average age of them was 63.9 ± 13.7 years, 269 (43.5%) were treated with heparinization during MT. Heparinization during MT didn't significantly influence recanalization rates, total ICH and long-term mortality (adjusted p > 0.05 for all). But sICH and distal embolization occurred more frequently (9.3 vs. 5.1%, adjusted p = 0.02; 7.1 vs. 3.1%, adjusted p = 0.04, respectively), while functional independence appeared less likely (39.8 vs. 47.4%, adjusted p = 0.01) in heparinization group than that in non-heparinization group. Multivariable logistic regression analyses showed that heparinization during MT was an independent predictor for sICH (Odds ratio 2.36 [1.19–4.67], p = 0.01) in addition to cardio-embolism stroke and posterior circulation stroke (PCS), and an independent predictor for poor outcome (Odds ratio 1.79 [1.23–2.59], p < 0.01) besides age, bridging intravenous thrombolysis, admission NIHSS, drinking and PCS. Conclusion: Heparinization during MT may be associated with increased risk of safety outcomes over sICH and distal embolization, as well as efficacy outcomes over long-term poor outcome. Further randomized controlled trials are needed.